An assessment of beach management units in combating illegal fishing in Lake Victoria, Tanzania: a case of Bukoba district - Kashililika, Edwin Wakisa (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Environmental Management (MSc EM) of the Mzumbe University